The Role of Awareness, Services, Socialization, Tax Audits and Sanctions in Taxpayer Compliance - Pradisa, Riska; Ferdiansyah, Ferdiansyah (Jurnal Akuntansi, 2025)
Purpose - The purpose of this study is to see how tax services, tax socialization, tax audits, and tax fines affect people's ability to pay their taxes. Design/Methodology/Approach - In this case, this research is quantitative. The population of this study consists of 431.006 people in South Tangerang City. A group of 400 taxpayers were selected. This research uses data collection techniques such as interviews, observations, and documentation. Data analysis technique using multiple linear regression was used with SPSS V25 to process data. Findings - The results of the study show that the influence of taxpayer awareness, fiscal services, tax socialization, tax audits and tax sanctions has a positive effect on WPOP compliance. Some taxpayer awareness, fiscal services, tax audits, and tax sanctions have a positive impact on individual taxpayer compliance and tax socialization has no effect on individual taxpayer compliance. Research Limitations/Implications - This research is limited to individual taxpayers at KPP Pondok Aren Pratama, so it cannot be generalized to all taxpayers. This study emphasizes the importance of awareness, service, audit, and taxation sanctions in improving compliance, while the effectiveness of socialization needs to be evaluated. Keywords: Fiscus Services, Individual Taxpayer Compliance, Taxpayer Awareness, Tax Audit and Tax Sanctions, Tax Socialization